Performance and security improvements of Dӧmӧsi’s cryptosystem - Khaleel, Ghassan; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Alshaikhli, Imad Fakhri Taha (CESER Publications, 2016)
Dӧmӧsi’s cryptosystem (Dӧmӧsi’s, 2008; Dӧmӧsi, November 11–14, 2009) is a new stream cipher based on finite automata without outputs. The cryptosystem uses specific deterministic finite accepters as secret keys for the encryption and decryption. Though this cryptosystem has been proven to be secure against different standard attacks (see (Kovacs´ and Penzes, January 27–30, 2010)), the proposed encryption algorithms in (Dӧmӧsi’s, 2008; Dӧmӧsi’s, November 11–14, 2009) involve exhaustive backtracking in order to generate ciphertexts. In this research, we propose a modified encryption algorithm, which improves performance of the system up to a better linear-time without effecting its security.